"I couldn't find it your honour, it mustn't be there!" – Tool errors, tool limitations and user error in digital forensics. Issue 6 (November 2018) - Horsman, Graeme
Abstract: The field of digital forensics maintains significant reliance on the software it uses to acquire and investigate forms of digital evidence. Without these tools, analysis of digital devices would often not be possible. Despite such levels of reliance, techniques for validating digital forensic software are sparse and research is limited in both volume and depth. As practitioners pursue the goal of producing robust evidence, they face the onerous task of both ensuring the accuracy of their tools and, their effective use. Whilst tool errors provide one issue, establishing a tool's limitations also provides an investigatory challenge leading the potential for practitioner user-error and ultimately a grey area of accountability. This article debates the problems surrounding digital forensic tool usage, evidential reliability and validation. Highlights: An examination of tool errors, tool limitations and user error in digital forensics. Digital forensic end user license agreements are discussed and evaluated. Suggestions for improving testing and defining tool limitations are made.